SPATIAL VARIABILITY OF THE GEOTECHNICAL PROPERTIES OF SOILS: A CASE STUDY OF ELIZADE UNIVERSITY (FUDMA JOURNAL OF SCIENCES, 2024)
Soil variability can alter the mechanical behaviour of foundations. It is therefore, necessary to conduct site investigations specific geotechnical analysis before any construction. This study evaluated selected engineering index and properties of soils at three different locations (sites) and depths withing Elizade University (EU), Ilara-Mokin. Five soil samples were collected from each of these locations and their engineering index and properties were determined. Statistical analysis namely Analysis of Variance (ANOVA) was utilised to determine the effects of location within the campus on the selected engineering properties. The mean and standard deviation (SD) of the engineering properties of soils collected within each site were also determined. The study revealed that plastic index (Pi), liquid limit (LL), moisture content (Mc), and plastic limit (Pl) were in the range of 4 to 32, 38 to 58.5, 11.6 to 29.04 %, 20 to 42 and respectively. The engineering index of the soil and engineering properties of the soil were significantly affected by the location with F14,42 equal to 2.592212, p was 0.008673 and F14, 42 equal to 3.210318 and p was 0.001719, respectively (which are less than 0.05). The high SD also showed that the soil properties have a wide range of values within same site, this was particularly so, in the case of the Atterberg’s limits, shear strength parameters and bearing capacities. The concluded that there is variability in the soil properties within the location.
Keywords: Bearing Capacity; Soil; Foundation Footings; Geotechnical Engineering Properties